2017
DOI: 10.1007/s11367-016-1258-7
|View full text |Cite
|
Sign up to set email alerts
|

LCA applied to nano scale zero valent iron synthesis

Abstract: Purpose Application of zero valent iron nanoparticles is an innovative technology for ground water treatment and soil remediation. There are several methods to synthesise nano scale zero valent iron (nZVI), namely through bottom-up methods which consists on chemical reactions using strong reducing agents. In this work, the environmental impacts and costs were determined for two methods, namely the traditional one that uses sodium borohydride and the green method that uses extracts obtained from natural product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…Martins et al. applied lifecycle assessment as an eco‐design strategy to evaluate the environmental performance of green syntheses of nZVI and identify the critical stages of the synthetic processes . Benign syntheses appear to have a lower environmental impact than traditional methods.…”
Section: Applications Of Sustainably Synthesized Nzvimentioning
confidence: 99%
“…Martins et al. applied lifecycle assessment as an eco‐design strategy to evaluate the environmental performance of green syntheses of nZVI and identify the critical stages of the synthetic processes . Benign syntheses appear to have a lower environmental impact than traditional methods.…”
Section: Applications Of Sustainably Synthesized Nzvimentioning
confidence: 99%
“…The use of green materials also fits well with the environment industry's paradigm shift toward nature based solutions (Song et al, 2019). The benefit of green synthesis was exemplified by Martins et al (2017), who used life cycle assessment (LCA) to reveal a 50% reduction in the total environmental impact of a green synthesized nano scale zero (EGCG, 36-40%), (-)Epigallocatechin (EGC 0.7%-2.3%) and (-)Epicatechin (EC 0.5-2.2%), which have bactericidal and antioxidant properties (Ahmmad et al, 2013). The ability of tea extract in the reduction of Fe was illustrated by Hoag et al (2009), who showed that as the reaction between Fe(NO 3 ) 3 and a tea extract occurred, the UV absorbance spectra shifted and the mixture changed from yellow to dark brown (Fig.…”
Section: Introductionmentioning
confidence: 74%
“…The environmentally friendlier compounds used in the green synthesis showed promising results compared to other green methods reported in the literature. 5 , 48 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The production of these compounds involves fossil fuel extraction, refining, and combustion, promoting the release and emission of solid, liquid, and gaseous wastes into the environment. 48 The contribution of iron(III) was related to a possible release of iron ions, 49 and the large amount used for the reduction to iron(II), considering that the latter compound was replaced by the C. citratus extract in the green synthesis. However, the low value was related to the iron(III) salt precursor composition since it was composed of chlorides instead of more toxic compounds such as sulfates.…”
Section: Results and Discussionmentioning
confidence: 99%